The complement C3‐C3aR pathway mediates microglia–astrocyte interaction following status epilepticus. Issue 5 (14th December 2020) - Wei, Yujia; Chen, Tingjun; Bosco, Dale B.; Xie, Manling; Zheng, Jiaying; Dheer, Aastha; Ying, Yanlu; Wu, Qian; Lennon, Vanda A.; Wu, Long‐Jun
Abstract: Gliosis is a histopathological characteristic of epilepsy that comprises activated microglia and astrocytes. It is unclear whether or how crosstalk occurs between microglia and astrocytes in the evolution of epilepsy. Here, we report in a mouse model of status epilepticus, induced by intracerebroventricular injection of kainic acid (KA), sequential activation of microglia and astrocytes and their close spatial interaction in the hippocampal CA3 region. Microglial ablation reduced astrocyte activation and their upregulation of complement C3. When compared to wild‐type mice, both C3 −/− and C3aR −/− mice had significantly less microglia–astrocyte interaction in response to KA‐induced status epilepticus. Additionally, KA‐injected C3 −/− mice had significantly less histochemical evidence of neurodegeneration. The results suggest that the C3‐C3aR pathway contributes to KA‐induced neurodegeneration by mediating microglia–astrocyte communication. The C3‐C3aR pathway may prove to be a potential therapeutic target for epilepsy treatment. Main Points: Microglia are required for astrocytes activation in experimental status epilepticus. C3 from astrocytes activates microglia via C3a receptors. Microglia–astrocyte interaction promotes gliosis and neuronal injury after seizures.